Landscape of in vivo Fitness-Associated Genes of Enterobacter cloacae Complex - Guérin, François; Lallement, Claire; Goudergues, Benoit; Isnard, Christophe; Sanguinetti, Maurizio; Cacaci, Margherita; Torelli, Riccardo; Cattoir, Vincent; Giard, Jean-Christophe (Frontiers in Microbiology, 2020)
Species of the Enterobacter cloacae complex (ECC) represent an increasing cause of hospital-acquired infections and commonly exhibit multiple antibiotic resistances. In order to identify genes that may play a role in its ability to colonize the host, we used the transposon-sequencing (Tn-seq) approach. To this end, a high-density random transposon insertion library was obtained from E. cloacae subsp. cloacae ATCC 13047, which was used to analyze the fitness of ca. 300,000 mutants in Galleria mellonella colonization model. Following massively parallel sequencing, we identified 624 genes that seemed essential for the optimal growth and/or the fitness within the host. Moreover, 63 genes where mutations resulted in positive selection were found, while 576 genes potentially involved in the in vivo fitness were observed. These findings pointed out the role of some transcriptional regulators, type VI secretion system, and surface-associated proteins in the in vivo fitness of E. cloacae ATCC 13047. We then selected eight genes based on their high positive or negative fold-changes and tested the corresponding deletion mutants for their virulence and ability to cope with stresses. Thereby, we showed that ECL_02247 (encoding the NAD-dependent epimerase/dehydratase) and ECL_04444 (coding for a surface antigen-like protein) may correspond to new virulence factors, and that the regulator ECL_00056 was involved in in vivo fitness. In addition, bacterial cells lacking the flagellum-specific ATP synthase FliI (ECL_03223) and the hypothetical protein ECL_01421 were affected for mobility and resistance to H2O2, respectively. All these results yield valuable information regarding genes important for infection process and stress response of E. cloacae ATCC 13047 and participate to a better understanding of the opportunistic traits in this bacterial pathogen.